2001
DOI: 10.1074/jbc.m009047200
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Pathways Involved in Phosphorylation and Activation of p70S6K Following Exposure to UVA Irradiation

Abstract: Ultraviolet light A (UVA) plays an important role in the etiology of human skin cancer, and UVA-induced signal transduction has a critical role in UVA-induced skin carcinogenesis. S6K co-immunoprecipitated with PI 3-kinase and possibly PDK1. The complex possibly possessed a partial basal level of phosphorylation, but not at MAPK sites, which was available for its activation by MAPKs in vitro. Thus, these results suggest that activation of MAPKs, like PI 3-kinase/mTOR, may be involved in UVA-induced phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 70 publications
5
93
0
Order By: Relevance
“…The stimulating effect upon UV exposure on S6K activity is rapamycin sensitive (Parrott and Templeton, 1999;Brenneisen et al, 2000;Ding et al, 2002;Huang et al, 2002). Interestingly, additional pathways (p38, ERK1/2, JNK and PI3K) may also affect S6K phosphorylation (Zhang et al, 2001). The activating effect can be attributed to the generation of reactive oxygen (ROS) species that accumulate in response to UV exposure, whereas pretreatment with ROS scavengers or antioxidants prevents S6K activation .…”
Section: Ultraviolet and Rosmentioning
confidence: 99%
“…The stimulating effect upon UV exposure on S6K activity is rapamycin sensitive (Parrott and Templeton, 1999;Brenneisen et al, 2000;Ding et al, 2002;Huang et al, 2002). Interestingly, additional pathways (p38, ERK1/2, JNK and PI3K) may also affect S6K phosphorylation (Zhang et al, 2001). The activating effect can be attributed to the generation of reactive oxygen (ROS) species that accumulate in response to UV exposure, whereas pretreatment with ROS scavengers or antioxidants prevents S6K activation .…”
Section: Ultraviolet and Rosmentioning
confidence: 99%
“…The activity of p70S6 kinase was assayed by using an immune complex in vitro kinase assay by modification of the methods of Zhang et al (52). Briefly, confluent muscle cells were rendered quiescent by incubation in serum-free DMEM for 24 h. Cells were stimulated with IGF-I (100 nM) for the indicated periods of time (0-24 h) in the presence or absence of various inhibitors.…”
Section: Culture Of Isolated Smooth Muscle Cells From Normal Human Jementioning
confidence: 99%
“…Kinases implicated in the phosphorylation and activation of p70 S6 kinase include mTOR (mammalian Target of Rapamycin) and PDK-1, which is responsible for phosphorylation of Thr229 (Dufner & Thomas, 1999). Recent studies have also indicated a role for p42/p44 MAPK, p38 MAPK and JNK in the phosphorylation and activation of p70 S6 kinase (Zhang et al, 2001). In addition, Zhang et al (2001) (Zhang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also indicated a role for p42/p44 MAPK, p38 MAPK and JNK in the phosphorylation and activation of p70 S6 kinase (Zhang et al, 2001). In addition, Zhang et al (2001) (Zhang et al, 2001). In this study, histamine-induced increases in p70 S6 kinase phosphorylation at Thr 421 /Ser 424 were completely blocked by PD 98059, wortmannin and LY 294002 but only partially sensitive to the mTOR inhibitor rapamycin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation